CONSIDERATION OF EMPLOYEE MOTIVATION IN THE ERA OF INDUSTRY 4.0 - Edith Primadiana Tedjokusumo (Politeknik Ubaya, 2019)
Industry 4.0 has been a hot issue for the development of worldwide trend, including in Indonesia. Indonesia stepped up to join the world’s crowd in the industry development by the statement of Indonesia’s President to be one of the top ten biggest global economies by 2030. In the same time, the government of Indonesia has called for how human resources should deal with industry of 4.0. The preparation ofentering Industry 4.0 has become really tremendous since last year. As a result, the human resources get a lot of attention. The objective of this paper is to identify the requirements in fulfilling the implementation of the Industry 4.0 by the fundamental of human resources, that is, employee motivation. This paper proposes the reflectionfor employee motivation towards Industry 4.0. It is also to represent the narration of thoughts and the followed-up in industry 4.0. The limitations of this paper are only on topics of employee motivation and industry 4.0.